Examining Latina IPV Survivors’ Help-Seeking Experiences: Unmet Needs and Lack of Culturally Competent Services - Avalos-Hernandez, Cristal Noemi (Crime & delinquency, 2024)
The current study examines the help-seeking experience of Latina intimate partner violence (IPV) survivors. By relying on data from a statewide IPV service needs assessment, this study answers the following research questions: (RQ1) What is the experience of seeking help from an IPV service agency like for Latina survivors? (RQ2) What are the most prevalent unmet needs among Latina survivors seeking help from an IPV service agency? Based on various rounds of thematic analysis, findings reveal there is a lack of culturally competent services and that housing, language barriers, and legal status are all interrelated factors that serve as a triple disadvantage for Latina IPV survivors.